Internal Communication Strategy and Its Influence on Employee Engagement - Poppy Wulandari; Blangi Intan Maharani; Yohana Yulianti Simbolon; Dwianita Dwianita; Ira Nur Dewita Siregar (Journal of Innovative and Creativity, 2025)
This study aims to analyze the influence of internal communication strategies on employee engagement and to identify the most effective communication approaches in enhancing employee involvement. The research employed a literature review method by examining journal articles, conference proceedings, and academic books published between 2019 and 2025. Literature sources were obtained from Google Scholar, Scopus, ResearchGate, and DOAJ, and were selected based on topic relevance, full-text availability, and alignment with the research focus. Data were analyzed using content analysis through thematic categorization. The findings indicate that internal communication strategies have a significant impact on employee engagement across three dimensions: cognitive, emotional, and behavioral. Three strategies were found to be the most effective: (1) digital channel–based communication that improves information access and accelerates feedback, (2) leadership-based communication that strengthens trust and emotional support, and (3) participatory two-way communication that fosters a sense of belonging and psychological ownership. Engagement formation occurs through role clarity, reinforced trust, and increased participation. In conclusion, internal communication serves as an organizational strategy that enhances employee motivation, loyalty, and contribution. Organizations must design communication patterns that are transparent, interactive, and participatory to optimize engagement.